Smart or Diverse Start-up Teams? Evidence from a Field Experiment - Hoogendoorn, Sander; Parker, Simon C.; van Praag, Mirjam (Organization Science, 2017)
This paper explores the relationship between cognitive abilities and team performance in a start-up setting. We argue that performance in this setting hinges on three tasks: opportunity recognition, problem solving, and implementation. We theorize that cognitive ability at the individual level has a positive effect on opportunity recognition and problem solving but no clear effect on implementation. Within teams, a combination of higher and lower cognitive ability levels may be productive insofar as some individuals can be assigned to mundane tasks (that are often involved in implementation), while others can be assigned to tasks that impose a greater cognitive load (problem solving or opportunity recognition). We present the results of a field experiment in which 573 students in 49 teams started up and managed real companies. We ensured exogenous variation in—otherwise random—team composition by assigning students to teams based on their measured cognitive abilities. Each team performed a variety of tasks, often involving complex decision making. The key result of the experiment is that the performance of start-up teams first increases and then decreases with ability dispersion. Strikingly, average team ability is not related to team performance.